'Maurine Blue' Lisianthus [Eustoma grandiflorum (Raf.) Shinn.] - A University of Florida Cultivar - Brent K. Harbaugh; John W. Scott (EDIS, 2005)
'Maurine Blue' is a heat-tolerant lisianthus developed at the University of Florida's Gulf Coast Research and Education Center in Bradenton, FL. Seedlings have been produced at temperatures ranging from 28 to 31°C without rosetting. This is document ENH960, a publication of the Environmental Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2003.